MIXING SEQUENCE EFFECT OF CEMENT COMPOSITES WITH CARBON FIBRES - Rizalman, Ahmad Nurfaidhi; Anthony, Eliezer Nevall; Thurairajah, Anand Ryan; S.Z.A., Sheikh Mohd Iqbal; Sulaiman, Muhd Fauzy (IIUM Engineering Journal, 2024)
Carbon fibres are widely recognised as reinforcement materials that effectively control cracks in concrete structures. Nonetheless, these fibres do not disperse uniformly inside the cement matrix, disrupting the mixture homogeneity. To address this concern, this study investigated two distinct mixing sequences of cement composites with carbon fibres. Two mixing sequences were investigated including the addition of fibres after cement (AC-CF) and the addition of fibres before cement (BC-CF). The surface topography of carbon fibres and the engineering properties of the cement paste were also examined. Consequently, carbon fibres in cement composite produced lower flowability due to the surface roughness. The AC-CF specimen demonstrated the highest hardened density at 28 days with 2679.22 kg/m3 followed by BC-CF and the control specimen with 2386.08 kg/m3 and 2278.36 kg/3, respectively. The AC-CF specimen also had the highest compressive strength at 28 days with 69.91 MPa, followed by BC-CF and the control specimen with 65.92 MPa and 63.20 MPa, respectively. Further, the flexural strength of the AC-CF specimen exhibited the highest strength with 10.86 MPa, followed by BC-CF and the control specimen with 9.35 MPa and 9.17, respectively. The fibre dispersion in AC-CF was also superior to BC-CF. Therefore, it can be concluded that the best mixing sequence is the addition of fibre after cement (AC-CF) because it had better fibre dispersion and engineering properties compared to the addition of fibre before cement (BC-CF). ABSTRAK: Gentian karbon lebih dikenali sebagai bahan bantuan yang berkesan dalam mengawal keretakan pada struktur konkrit. Walau bagaimanapun, gentian ini tidak tersebar secara seragam di dalam matrik simen dan akan mengganggu kehomogenan campuran. Bagi mengatasi masalah ini, kajian ini mengkaji tentang dua susunan campuran berbeza simen komposit dengan gentian karbon. Dua susunan campuran ini adalah melalui penambahan gentian selepas simen (AC-CF) dan penambahan gentian sebelum simen (BC-CF). Permukaan topografi gentian karbon dan sifat kejuruteraan pes simen turut diperiksa. Kajian mendapati bahawa gentian karbon dalam komposit simen mengurangkan kebolehaliran pes simen disebabkan oleh kekasaran pada permukaan gentian. Spesimen AC-CF menunjukkan ketumpatan pengerasan tertinggi pada hari ke-28 dengan 2679.22 kg/m3 diikuti spesimen BC-CF dan spesimen kawalan sebanyak 2386.08 kg/m3 dan 2278.36 kg/m3, masing-masing. Spesimen AC-CF juga mempunyai kekuatan mampatan tertinggi pada hari ke-28 dengan 69.91 MPa, diikuti oleh spesimen BC-CF dan spesimen kawalan sebanyak 65.92 MPa dan 63.20 MPa, masing-masing. Seterusnya, kekuatan lenturan spesimen AC-CF menunjukkan kekuatan tertinggi dengan 10.86 MPa, diikuti spesimen BC-CF and spesimen kawalan dengan 9.35 MPa dan 9.17 MPa, masing-masing. Penyebaran gentian dalam AC-CF juga lebih baik daripada BC-CF. Oleh itu, kajian ini merumuskan bahawa susunan campuran terbaik adalah dengan penambahan gentian selepas simen (AC-CF) kerana ia mempunyai kekuatan lenturan gentian terbaik dan sifat kejuruteraan berbanding penambahan gentian sebelum simen (BC-CF).